Chemical Preparation of Beta Calcium Sulfate Hemihydrate Granules with a Special Particle Size as Bone Graft Material - Naser Sargolzaie; Javad Sargolzaie; Nasrollah Saghravanian (Mashhad University of Medical Sciences, 2014)
Introduction: Beta calcium sulfate hemihydrate (BCSH), which is commonly known as "Gypsum plaster" has long been used as bone graft material because of its excellent biocompatibility and the ability for bone regeneration. Several methods have been used for the preparation of BCSH, including heat treatment of calcium sulfate dihydrate with water, application of inorganic acids or condensed inorganic salt solutions under high or atmospheric pressure. As a bone graft, it is preferred that the BCSH powder has a granular form for the purpose of manipulation, bio-mechanical properties and ease of injection. Methods: For this study granules of BCSH in the size of 500 to 700 micrometers were manufactured and sterilized using gamma ray. For assessing the regeneration of thismaterial, six rabbits were selected and granules were injected in the bone defects that were made using diamond bur in their skull under general anesthesia. Biopsies for histological evaluations were done 3, 6, 9, 12, 14 and 16 months following surgery. Results: At the third month time-point, remodeling of the BCSH was evident, and complete newly formed bone was seen in the region of the defect. Conclusion: The results of this study demonstrated that BCSH had a good biocompatibility without inducing an inflammatory response and promoted bone healing.